2010
DOI: 10.1159/000319506
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Infection Decreases Calbindin, Decreases Purkinje Cell Volume and Density and Produces Long-Term Motor Deficits in Sprague-Dawley Rats

Abstract: The cerebellum is involved in the control of motor functions with Purkinje cells serving as the only output from the cerebellum. Purkinje cells are important targets for toxic substances and are vulnerable to prenatal insults. Intrauterine infection (IUI) has been shown to selectively target the developing cerebral white matter through lesioning, necrosis and inflammatory cytokine activation. Developmental and cognitive delays have been associated with animal models of IUI. The aim of this study was to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 97 publications
(57 reference statements)
6
11
0
Order By: Relevance
“…We report here that cerebellar width, individual ZII+/− PC stripe widths, and PC numbers are increased in prenatally poly(I:C)-exposed offspring of both sexes. Previous findings indicate reduced numbers of PCs following MIA (e.g., [47,63]). In contrast, we find greater numbers of PCs in the poly(I:C)-exposed mice compared to saline controls at all ages tested.…”
Section: Discussionmentioning
confidence: 88%
“…We report here that cerebellar width, individual ZII+/− PC stripe widths, and PC numbers are increased in prenatally poly(I:C)-exposed offspring of both sexes. Previous findings indicate reduced numbers of PCs following MIA (e.g., [47,63]). In contrast, we find greater numbers of PCs in the poly(I:C)-exposed mice compared to saline controls at all ages tested.…”
Section: Discussionmentioning
confidence: 88%
“…Rat models of prenatal bacterial infection have also led to structural and biochemical brain abnormalities in the offspring of exposed rats. Recently, Wallace et al (2010) injected pregnant rats with Escherichia coli ( E. coli ) on E17. While prenatal infection with E. coli did not affect birth weight, the authors did observe “surface righting and negative geotaxis” in the offspring (Wallace et al, 2010).…”
Section: Animal Models Infected With Lpsmentioning
confidence: 99%
“…Recently, Wallace et al (2010) injected pregnant rats with Escherichia coli ( E. coli ) on E17. While prenatal infection with E. coli did not affect birth weight, the authors did observe “surface righting and negative geotaxis” in the offspring (Wallace et al, 2010). Interestingly, infected offspring exhibited reduced Purkinje cell counts, density, and volume, and decreased calbindin, a calcium-binding protein expressed by Purkinje cells in the cerebellum and known for its involvement in motor coordination (Barski et al, 2003).…”
Section: Animal Models Infected With Lpsmentioning
confidence: 99%
“…The inflammatory response has been implicated in the genesis of fetal brain injury in humans [1, 5, 15, 29, 30] as well as in experimental animal models [6367]. However, some recent studies [4, 6870] reported that acute histologic chorioamnionitis was not an independent risk factor for the development of IVH.…”
Section: Introductionmentioning
confidence: 99%